Geraniol ester loaded-nanoemulsions: Exploring enzymatic synthesis, biocompatibility, antioxidant potential, and antimicrobial activity - Remonatto, Daniela; do Amaral, Stéphanie Rochetti [UNESP]; do Nascimento, João Francisco C. [UNESP]; Dutra, Jessyca A.P. [UNESP]; Chorilli, Marlus [UNESP]; Bassan, Juliana C.; Oliveira, José Vladimir; Filho, Josemar G. Oliveira; Mattoso, Luiz H.C.; Primo, Fernando L. [UNESP]; de Paula, Ariela V. [UNESP] (Elsevier, 2025)
This study aimed to synthesize geranyl acetate (GA) and geranyl cinnamate (GC) by enzymatic esterification using Lipura Flex lipase for the development of nanoemulsions (NE) and evaluate their antimicrobial and antioxidant activities and biocompatibility with fibroblast cells. A 22 factorial central composite rotatable design was used to maximize ester synthesis. For GA synthesis, optimal conditions were 15 % (w/w) Lipura Flex, a 1:3 molar ratio of acetic acid to geraniol, 60 °C, and a reaction time of 1 h, which afforded a relative yield of 99.43 % ± 1.8 % (w/w). For GC synthesis, optimal conditions were 15 % (w/w) Lipura Flex, a 1:5 molar ratio of cinnamic acid to geraniol, 70 °C, and 24 h of reaction, resulting in a relative yield of 100 % ± 1.09 %. NEs were successfully developed. Particle sizes ranged from 70 to 350 nm. NEs remained stable for 30 days. GANE showed higher biocompatibility with fibroblast cells (100 % viability) than non-encapsulated GA (30 % reduction in cell viability). GCNE also demonstrated good biocompatibility, resulting in cell viability values above 90 %. Both NE systems exhibited considerable antioxidant (50 % free radical inhibition) and antimicrobial properties. GANE had greater antimicrobial activity than GCNE, attributed to its smaller droplet size (73.3 nm versus 302.0 nm). These results highlight the potential of ester-loaded nanoemulsions as bioactive materials for innovative applications in pharmaceutical and cosmetic formulations, emphasizing their relevance for future advancements in nanotechnology-driven product development.